Komparasi Keterampilan Menulis Teks Deskripsi dengan Keterampilan Menulis Teks Cerita Fantasi Siswa Kelas VII SMP Negeri 7 Padang - Velia Febrianti; Harris Effendi Thahar (Universitas Negeri Padang, 2020)
ABSTRACT This article reveals the comparison of writing description text skills with fantasy stories of seventh grade students of SMP Negeri 7 Padang. The objectives of the study are four. First, it describes students' writing text description skills. Second, describe the writing skills of students' fantasy text. Third, analyze the comparison of writing description text skills with students' fantasy stories. Fourth, analyze the factors that cause differences in writing description text skills with fantasy stories. The design of this study is comparative. The study population was students of class VII SMP 7 Padang who registered in the 2019/2020 school year as many as 255 students. The research sample of 48 students, determined through simple random sampling technique (20% of the population). The research data were the score of writing skills as well as the results of interviews with students about the skills of writing description texts and fantasy stories. Data obtained through performance tests and interviews. There are four research results. First, the students' writing description text skills are more than adequate (LdC) qualifications with an average of 75.26. Second, the students' ability to write fantasy text is in good qualifications (B) with an average of 80.86. Third, there are differences in writing description text skills with students' fantasy stories. Fourth, there are four factors that cause differences in the two writing skills of the text, namely elements of facts and opinions, the use of a variety of standard and non-standard languages, talents/interests, and educators in the teaching and learning process.Kata kunci: Keterampilan, Teks Deskripsi, Teks Cerita Fantasi, Menulis, Komparasi